Neurosarcoidosis in an adult man with a family history of MS: A case report - Omid Mirmosayyeb; Mahtab Mohammadzamani; Sara Bagherieh; Elham Moases Ghaffary; Elham Sadat Azimi; Aysa Shaygannejad; Vahid Shaygannejad (Clinical Case Reports, 2023)
Key clinical message According to this report, a biopsy revealed a diagnosis of neurosarcoidosis in a patient with a history of MS. The development of the disease can be slowed down by early diagnosis and appropriate treatment. Abstract Neurosarcoidosis is a rare type of sarcoidosis that affects the central nervous system (CNS). Herein, we present a case of neurosarcoidosis with a history of multiple sclerosis (MS). Based on the pathological findings of the biopsy, a diagnosis of neurosarcoidosis was established. The administration of appropriate treatment at an early stage can assist in decelerating its progression.